Interpreting Financial Market Crashes as Earthquakes: A New early Warning System for Medium Term Crashes - Francine Gresnigt; Erik Kole; Philip Hans Franses (Tinbergen Institute, 2014)
We propose a modeling framework which allows for creating probability predictions on a future market crash in the medium term, like sometime in the next five days. Our framework draws upon noticeable similarities between stock returns around a financial market crash and seismic activity around earthquakes. Our model is incorporated in an Early Warning System for future crash days. Testing our EWS on S&P 500 data during the recent financial crisis, we find positive Hanssen-Kuiper Skill Scores. Furthermore our modeling framework is capable of exploiting information in the returns series not captured by well known and commonly used volatility models. EWS based on our models outperform EWS based on the volatility models forecasting extreme price movements, while forecasting is much less time-consuming.
Keywords: C13; C15; C53; G17; 330; Financial crashes; Hawkes process; self-exciting process; Early Warning System